The Role of Plant Litter in Driving Plant-Soil Feedbacks - Veen, G. F. (Ciska); Fry, Ellen L.; ten Hooven, Freddy C.; Kardol, Paul; Morriën, Elly; De Long, Jonathan R. (Frontiers in Environmental Science, 2019)
Most studies focusing on plant-soil feedbacks (PSFs) have considered direct interactions between plants, abiotic conditions (e. g., soil nutrients) and rhizosphere communities (e.g., pathogens, mutualists). However, few studies have addressed the role of indirect interactions mediated by plant litter inputs. This is problematic because it has left a major gap in our understanding of PSFs in natural ecosystems, where plant litter is a key component of feedback effects. Here, we propose a new conceptual framework that integrates rhizosphere- and litter-mediated PSF effects. Our framework provides insights into the relative contribution of direct effects mediated by interactions between plants and soil rhizosphere organisms, and indirect effects between plants and decomposer organisms mediated by plant root and shoot litter. We distinguish between three pathways through which senesced root and shoot litter may influence PSFs. Specifically, we examine: (1) physical effects of litter (layer) traits on seed germination, soil structure, and plant growth; (2) chemical effects of litter on concentrations of soil nutrients and secondary metabolites (e.g., allelopathic chemicals); and (3) biotic effects of saprotrophic soil communities that can perform different functional roles in the soil food web, or that may have specialized interactions with litter types, thereby altering soil nutrient cycling. We assess the role of litter in PSF effects via physical, chemical and biotic pathways to address how litter-mediated feedbacks may play out relative to, and in interaction with, feedbacks mediated through the plant rhizosphere. We also present one of the first experimental studies to show the occurrence and species-specificity of litter-mediated feedbacks and we identify critical research gaps. By formally incorporating the plant-litter feedback pathway into PSF experiments, we will further our understanding of PSFs under natural conditions.